2008
DOI: 10.1016/j.obhdp.2007.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Why the unskilled are unaware: Further explorations of (absent) self-insight among the incompetent

Abstract: People are typically overly optimistic when evaluating the quality of their performance on social and intellectual tasks. In particular, poor performers grossly overestimate their performances because their incompetence deprives them of the skills needed to recognize their deficits. Five studies demonstrated that poor performers lack insight into their shortcomings even in real world settings and when given incentives to be accurate. An additional meta-analysis showed that it was lack of insight into their own… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
417
3
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 530 publications
(484 citation statements)
references
References 65 publications
(69 reference statements)
31
417
3
7
Order By: Relevance
“…The present study provided new evidence that low performing students suffer from functional overconfidence in their postdiction judgments of performance, but that they also seem to generally be aware that their metacomprehension is not well calibrated. As such our data lend more credence to the hypothesis that the "unskilled are aware" (Miller & Geraci, 2011) rather than the hypothesis that the "unskilled are unaware" (e.g., Dunning et al, 2003;Ehrlinger et al, 2008). Given that low performing students seem fairly aware of their own metacomprehension deficits both before and after testing, but that their confidence may improve under certain conditions, future research should include interventions which focus on (a) increasing awareness of the connection of confidence to actual performance, and (b) requiring students to practice reflecting on past performance more, rather than only being concerned with predicting upcoming performance.…”
Section: Subjective Confidence In Postdictionssupporting
confidence: 51%
See 3 more Smart Citations
“…The present study provided new evidence that low performing students suffer from functional overconfidence in their postdiction judgments of performance, but that they also seem to generally be aware that their metacomprehension is not well calibrated. As such our data lend more credence to the hypothesis that the "unskilled are aware" (Miller & Geraci, 2011) rather than the hypothesis that the "unskilled are unaware" (e.g., Dunning et al, 2003;Ehrlinger et al, 2008). Given that low performing students seem fairly aware of their own metacomprehension deficits both before and after testing, but that their confidence may improve under certain conditions, future research should include interventions which focus on (a) increasing awareness of the connection of confidence to actual performance, and (b) requiring students to practice reflecting on past performance more, rather than only being concerned with predicting upcoming performance.…”
Section: Subjective Confidence In Postdictionssupporting
confidence: 51%
“…Recent research on this issue has focused primarily on predictions rather than postdictions, and the findings have been mixed. One account has argued that academically poorer students are "double cursed" (Ehrlinger et al, 2008) in that they are unskilled and unaware; however, other researchers have found that poor performing students are unskilled but very much aware of their poor metacognitive judgments (Miller & Geraci, 2011). One of the aims of the present study was to investigate this issue by providing evidence to help adjudicate between these two competing explanations, with a particular focus on postdiction accuracy and confidence judgments.…”
Section: Postdiction Accuracy and Confidence In Postdiction Judgmentsmentioning
confidence: 87%
See 2 more Smart Citations
“…We measured participants' assessment of their own abilities in music with a two-item scale that captured their general sense of their musical talent on the Times 1, 2, and 3 surveys. Self-estimate of ability measures typically ask participants to rate their ability relative to a salient, proximal reference group, for instance, to other people the same age (Ackerman, Beier, & Bowen, 2002), other students in their class, or other competitors in the same tournament (Ehrlinger et al, 2008). In line with this previous research, the only salient, proximal reference group in the present study was peers in the same musical specialty at the 2001 summer music program (e.g., others who play the same instrument), to whom participants compared themselves on the Times 1, 2, and 3 surveys.…”
Section: Methodsmentioning
confidence: 99%